Enhancing the stability of lutein emulsions with a water-soluble antioxidant and a oil-soluble antioxidant - Yujiao Wang; Xiangxiang Zhang; Manlin Yan; Quanyu Zhao (Heliyon, 2023)
Lutein is critical for protecting the eye against light damage. The low solubility and high sensitivity of lutein to environmental stresses prevent its further application. The hypothesis is that the combination of one water-soluble antioxidant and one oil-soluble antioxidant will be beneficial to improve the stability of lutein emulsions. A low-energy method was performed to prepare lutein emulsions. The combination of a lipid-soluble antioxidant (propyl gallate or ethylenediaminetetraacetic acid) and a water-soluble antioxidant (tea polyphenol or ascobic acid) were investigated for improving the lutein retention rates. It was shown that the highest lutein retention rate was achieved by using propyl gallate and tea polyphenol, 92.57%, at Day 7. It was proven that the lutein retention rates of emulsions with propyl gallate and tea polyphenol were 89.8%, 73.5% and 55.2% at 4 °C, 25 °C and 37 °C, respectively, at Day 28. The current study is helpful to prepare for the further application of lutein emulsions for ocular delivery.